Assessing the performance of density functional theory in optimizing molecular crystal structure parameters. Issue 2 (17th March 2014) - Binns, Jack; Healy, Mary R.; Parsons, Simon; Morrison, Carole A.
<x xml:space="preserve">Abstract</x> This paper assesses the performance of plane‐wave density functional theory calculations at returning reliable structural information for molecular crystal structures where the primary intermolecular interactions are either hydrogen bonding or dispersion interactions. The computed structures are compared with input structures obtained from the Cambridge Structural Database, and assessed in terms of crystal packing similarities, unit‐cell volume and shape, short contact distances and hydrogen‐bond distances. The results demonstrate that the PBE functional [Perdew, Burke & Ernzerhof (1996). Phys. Rev. Lett.77, 3865–3868] with Tkatchenko and Scheffler's `TS' dispersion correction [Tkatchenko & Scheffler (2009). Phys. Rev. Lett.102, 073005] is capable of returning reliable full structural optimizations, in which both atomic positions and unit‐cell vectors are free to optimize simultaneously.